From Discussion Forums to eMeetings: Integrating High Touch Strategies to Increase Student Engagement, Academic Performance, and Retention in Large Online Courses - Gay, Glenda H.; Betts, Kristen (Online Learning, 2020)
Student engagement and group work are critical to developing competencies, deeper learning, and attributes that align with 21st-century skills. Group work is particularly important for future employment in an increasingly competitive and dynamic workforce. A new capstone group work assignment using Online Human Touch (OHT) strategies was integrated into an Information Systems course at a regional university in the Caribbean. The course typically enrolls 250-300+ students per semester with one instructor. The assignment simulated a real-world business ‘eMeeting’ to proactively increase student engagement and retention. Quantitative data was collected three years prior to, and three years after the new ‘eMeeting’ format. Qualitative feedback after the integration shows significant increases in student engagement, while results and data show improved academic performance, higher scores on the standardized final exam and decreases in attrition. Integrating group assignments in large courses with real-world requirements, not only provide students with the opportunity to apply the knowledge, skills, and experience gained throughout the course, but enhance key soft skills sought by employers including problem-solving, ability to work in teams, communication, leadership, and time management.